2019
DOI: 10.1063/1.5111321
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure synthesis of superhard and ultrahard materials

Abstract: A brief overview on high-pressure synthesis of superhard and ultrahard materials is presented in this tutorial paper. Modern high-pressure chemistry represents a vast exciting area of research which can lead to new industrially important materials with exceptional mechanical properties. This field is only just beginning to realize its huge potential, and the image of "terra incognita" is not misused. We focus on three facets of this expanding research field by detailing: (i) the most promising chemical systems… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 133 publications
(197 reference statements)
0
19
0
Order By: Relevance
“…The AFM results revealed that the (T2) sample contained smaller particles (mean particle size), resulting in a more uniform distribution across the surface [ 48 , 49 ]. The area of contact between the film and the substrate increased.…”
Section: Resultsmentioning
confidence: 99%
“…The AFM results revealed that the (T2) sample contained smaller particles (mean particle size), resulting in a more uniform distribution across the surface [ 48 , 49 ]. The area of contact between the film and the substrate increased.…”
Section: Resultsmentioning
confidence: 99%
“…Boron-rich compounds attracted much attention in the past years for the design of new useful materials combining high hardness, toughness, and resistance to extreme mechanical, thermal and radiation conditions [ 6 , 67 ]. In particular, numerous attempts have been made to fulfill the hardness gap between two reference superhard materials, i.e., polycrystalline diamond (H V ~80–120 GPa, which is a typical value range of good-quality sintered samples) and two times less harder c-BN (H V ~40–60 GPa for polycrystalline ingots, also these hardness values for diamond and c-BN can be higher for single crystal faces and nanostructured ingots) [ 67 ].…”
Section: In Situ Large-volume High-pressure Synthesesmentioning
confidence: 99%
“…Since the success of these pioneering studies, high-pressure synthesis promoted a large number of new classes of materials with outstanding properties, recoverable at ambient conditions. The most remarkable are: (1) new superhard phases [ 6 ] with electrical conductivity like c-BC 5 [ 7 ] or even with non-carbon composition—like nanostructured phases of c-BN [ 8 , 9 ] and high pressure boron allotrope γ-B [ 10 ]; (2) new multiferroic materials (like BiMnO 3 , BiAlO 3 , BiGaO 3 , BiFeO 3 [ 11 ]; (3) new thermoelectric compounds (silicon clathrates [ 12 ] or CoSb 2 . 75 Te 0 .…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, there is a growing demand for other advanced materials that stimulated the search for novel ultra-hard thermally and chemically stable phases (cf. [1,[2][3][4] and references therein).…”
Section: Introduction and Contextmentioning
confidence: 99%